The European Cardiac Resynchronization Therapy Survey: comparison of outcomes between de novo cardiac resynchronization therapy implantations and upgrades - Bogale, Nigussie; Witte, Klaus; Priori, Silvia; Cleland, John; Auricchio, Angelo; Gadler, Fredrik; Gitt, Anselm Kai; Limbourg, Tobias; Linde, Cecilia; Dickstein, Kenneth (European journal of heart failure, 2011)
Aims Cardiac resynchronization therapy (CRT) is an effective treatment for a subset of patients with chronic heart failure. Data on the benefit of CRT in heart failure patients with previous right ventricular pacemakers or standard defibrillators are sparse. Methods and results The European (HFA, Heart Failure Association/EHRA, European Heart Rhythm Association) CRT Survey enrolled patients from 141 centres in 13 countries in Europe collecting baseline demographic, echocardiographic, clinical, and implant data, with follow-up at ∼1 year. The present analysis reports implantation data and 1 year outcomes regarding New York Heart Association (NYHA) class, global patient assessment, hospitalizations, complications, and mortality in patients undergoing de novo CRT implantations compared with those receiving an upgrade of a previously implanted device (pacemaker or implantable cardioverter-defibrillators). This analysis includes 2367 CRT implant procedures of which 692 (28%) were upgrades to CRT. Distribution of NYHA functional class and left ventricular function were similar between the groups. Procedural duration was also similar, although fluoroscopy time was shorter in the ‘upgrades’. There was no difference in the frequency of peri-procedural complications. There were similar improvements in NYHA functional class and similar reduction in QRS duration, but more patients reported unchanged global assessment status in the upgraded group. Total and cause-specific mortality at 1 year was low and the same in both groups. Conclusions More than one quarter of all CRT procedures are upgrades from existing systems, although this group has not been subject to randomized clinical trials. Our data suggest that there are no significant differences in clinical outcomes or complication rates between upgrades and de novo procedures. Clinical study no NCT 01185392